EVALUATION OF THE MADRASAH EDUCATION QUALITY REFORM (MEQR) PROGRAMME IN THE MINISTRY OF RELIGION OF SOUTH SUMATRA PROVINCE - Bermawi, Ahmad; Zainuri , Ahmad; Isnaini , Muhammad (Sekolah Tinggi Agama Islam Al Hidayah, 2025)
Background: The Madrasah Education Quality Reform (MEQR) programme is a strategic initiative of the Ministry of Religious Affairs in improving the quality of madrasah education nationally, including in South Sumatra Province. This study aims to evaluate the effectiveness of MEQR, especially in the aspects of planning, implementation, monitoring, and its impact on strengthening the quality of madrasah. Research Objectives: This study aims to evaluate the effectiveness of MEQR, especially in the aspects of planning, implementation, monitoring, and its impact on strengthening the quality of madrasah. Methods: The study used a descriptive qualitative approach with data collection techniques through in-depth interviews, observation, and documentation studies. Informants included programme implementing officials at the provincial and district/city levels, madrasah heads, and educators. Results: The results showed that MEQR made a significant contribution in increasing the capacity of data-based management, implementing EMIS and e-RKAM systems, and developing madrasah facilities and infrastructure. The programme also promotes efficient governance and transparency in budget use. However, a number of obstacles are still encountered, especially related to cross-level coordination, limited human resources, and programme sustainability after external support. Conclusion: In general, the implementation of MEQR in South Sumatra Province can be categorised as quite effective, but requires strengthening in technical assistance, continuous monitoring, and active involvement of all stakeholders. These efforts are important so that madrasah education reform does not only have a short-term impact, but also sustainable in improving the quality and competitiveness of madrasah in the digital era.